THE EFFECT OF FLOW RATE AND RESIDENCE TIME IN A BAFFLED ANAEROBIC REACTOR ON AMMONIA REDUCTIONIN SLAUGHTERHOUSES - Dian - Safitri; Hery Setyobudiarso; Candra Dwiratna Wulandari (Purifikasi, 2026)
Slaughterhouse wastewater contains high concentrations of ammonia due to the degradation of organic compounds, which has the potential to cause environmental pollution if not properly treated. This study aims to analyze the effect of variations in flow rate and hydraulic residence time on the performance of an Anaerobic Baffled Reactor (ABR) in reducing ammonia concentrations in slaughterhouse wastewater. The study was conducted experimentally using a laboratory-scale Anaerobic Baffled Reactor (ABR) reactor measuring 85 cm x 40 cm x 30 cm with five compartments. The reactor was operated continuously at two flow rate variations, namely 34 L/hour and 38 L hour, and two residence time variations, namely 6 hours and 12 hours. The main parameter analyzed was the ammonia (NH3-N) concentration. The results showed that the flow rate and residence time had a significant effect on the efficiency of ammonia reduction. At a flow rate of 34 L/hour, the ammonia reduction efficiency was 55% at a residence time of 6 hours and increased to 70% at a residence time of 12 hours. Meanwhile, at a flow rate of 38 L/hour, the ammonia reduction efficiency was 48% at a residence time of 6 hours and increased to 67% at a residence time of 12 hours. The most effective operational conditions were obtained at a flow rate of 34 L/hourwith a residence time of 12 hours, which resulted in an ammonia concentration in the effluent of 22 mg N/L and met quality standards. These results indicate that the ABR reactor has the potential to be applied as an effective slaughterhouse liquid waste treatment technology with optimal flow rate and residence time settings.